Improved vehicle-for-grid (iV4G) mode: novel operation mode for EVs battery chargers in smart grids - Monteiro, Vítor Duarte Fernandes (2019)
The experimental validation of a novel operation mode for electric vehicles (EVs) to support the grid power quality is presented. The proposed operation mode, denominated improved vehicle-for-grid (iV4G), is directly associated with the EVs operation aiming the compensation of power quality problems associated with current harmonic distortion and reactive power, improving the total power factor of the electrical installation. Simultaneously with the proposed iV4G, where the EV injects current harmonics and provides reactive power, the EV can exchange active power with the grid (grid-to-vehicle, G2V, to charge the batteries or vehicle-to-grid, V2G, to deliver energy back to the power grid). In this paper, the proposed iV4G operation mode is experimentally validated with a developed EV battery charger prototype connected to an electrical installation of 230 V, 16 A, 50 Hz. The control strategies of the iV4G operation mode and the used prototype are described in detail along the paper. The achieved results confirm the feasibility and good performance of the proposed iV4G operation mode, working alone, and also when associated with the G2V and V2G operating modes.